Quantum Key Distribution: Simulation and Characterizations - Jasim, Omer K.; Abbas, Safia; El-Horbaty, El-Sayed M.; Salem, Abdel-Badeeh M. (Procedia computer science, 2015)
All traditional cryptographic algorithms used in the network communication environments, relied on mathematical models and computational assumptions, are actually unsafe and apt by many attackers (quantum and man-in-the-middle attacks). Therefore, nowadays Quantum Key Distribution (QKD) promises a secure key agreement by using quantum mechanical systems. QKD becomes a significant trend of new cryptographic revolution. This paper explains how cryptography exploits the quantum mechanics in order to achieve an encryption/decryption process. Additionally, this paper provides a standard simulation for QKD-BB84 protocol and describes improvement key generation and key distribution mechanisms. Then, validation, results and efficiency of BB84 protocol are presented using different security configurations. Finally, our results indicated that the QKD is susceptible to corporate with different security applications and achieve the key availability for such applications. However, it suffers from the higher rate of authentication cost.